THE DEVELOPMENT OF LINEAR INSTRUCTIONAL MULTIMEDIA OF CLASSROOM MANAGEMENT AND LEADING SMALL GROUP DISCUSSION SKILLS FOR MICROTEACHING CLASS IN ENGLISH EDUCATION DEPARTMENT UNDIKSHA - ., Putu Reuni Yuliana; ., I G A Lokita P Utami, S.Pd.; ., Ni LP. Eka Sulistia Dewi, S.Pd. M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk mengembangkan multimedia pembelajaran linear untuk keterampilan mengelola kelas dan keterampilan membimbing diskusi kelompok kecil di kelas microteaching di jurusan Pendidikan Bahas Inggris UNDIKSHA. Desain penelitian dan pengembangan (R&D) oleh Dick and Carey diadaptasi dalam penelitian ini. Langkah yang dilakukan adalah analisis kebutuhan, analisis pembelajaran, analisis siswa dan lingkungannya, merumuskan tujuan khusus, mengembangkan instrument penilaian, mengembangkan strategi pembelajaran, mengembangkan materi pembelajaran, melakukan penilaian formatif, dan revisi produk. Hasil multimedia pembelajaran memperlihatkan bahwa multimedia yang sesuai dengan kebutuhan mahasiswa Pendidikan Bahasa Inggris UNDIKSHA adalah multimedia pembelajaran yang isi pada simulasi mengenai pembelajaran bahasa Inggris, menggunakan bahasa Inggris sebagai ahasa penghantar, and tingkatan siswa pada simulasi adalah tingkat SMA. Lalu kualifikasi multimedia pembelajaran linear yang dihasilkan adalah “sangat baik” dengan presentase keseluruhan 87.00% untuk multimedia pembelajaran keterampilan mengelola kelas dan 87.03% untuk keterampilan membimbing diskusi kelompok kecil. Kata Kunci : Penelitian dan pengembangan, multimedia pembelajaran linear, keterampilan mengelola kelas, keterampilan membimbing diskusi kelompok kecil. This research is an Education Research and Development which aimed at developing linear instructional multimedia of classroom management skill and leading small group discussion skill for microteaching class in English Education Department UNDIKSHA. To develop the instructional multimedia, the Research and Development (R&D) design by Dick & Carey was adapted. The steps done in developing the product were started with identifying instructional goals, conducting instructional analysis, analyzing learners and contexts, writing performance objectives, developing assessment instruments, developing instructional strategy, developing instructional materials, conducting formative evaluation, and the last revising product. Moreover, the result showed that the linear instructional multimedia which is suitable for the English Education Department UNDIKSHA students’ needs is an instructional multimedia by which the content in the illustration/simulation of the skill components is about English language learning, the level of the students (setting) in the simulation is senior high school level, and the instructional language used is English. Then, the linear instructional multimedia has very good qualification with whole percentage (F/N) of 87.00% for classroom management skill and 87.03% for leading small group discussion skill linear instructional multimedia.keyword : research and development, linear instructional multimedia, classroom management skill, small group discussion skill